Sexual abuse: A practical theological study, with an emphasis on learning from transdisciplinary research - Human, Heidi (HTS teologiese studies, 2015)
This article illustrates the practical usefulness of transdisciplinary work for practical theology by showing how input from an occupational therapist informed my understanding and interpretation of the story of Hannetjie, who had been sexually abused as a child. This forms part of a narrative practical theological research project into the spirituality of female adult survivors of childhood sexual abuse. Transdisciplinary work is useful to practical theologians, as it opens possibilities for learning about matters pastors have to face, but may not have knowledge about. A short retelling of Hannetjie’s story is given to provide information about the context of the research. Next, the transdisciplinary process that was followed is mentioned, and the questions that the transdisciplinary team had to respond to are discussed. Following that, I focus more specifically on the occupational therapist’s answers, and the knowledge gained from her contribution, as an example of how a co-researcher from a divergent discipline can inform a theological study. In this case, knowledge was shared about sensory integration and how the brain processes traumatic stimuli, such as sexual abuse. Lastly, the interrelationship between Hannetjie’s body stories, mind stories and spirit stories is discussed to show how the learning received from occupational therapy affected my thinking about Hannetjie’s stories and the relationships between them. Thus, it is concluded that transdisciplinary work has great value for practical theology, especially in the pastor’s daily work with people who are struggling with difficult stories, because we cannot listen to people’s spirit stories in isolation. They are inextricably intertwined with all our stories about ourselves.